Characteristics of patients with haematological and breast cancer (1996–2009) who died of heart failure‐related causes after cancer therapy. (17th July 2016) - Versace, Vincent L.; Berry, Narelle M.; Chowdhury, Munir H.; Ullah, Shahid; McCarthy, Alexandra L.; Atherton, John J.; Koczwara, Bogda; Roder, David; Clark, Robyn A.
Abstract: Aims: To describe the characteristics and time to death of patients with breast or haematological cancer who died of heart failure (HF) after cancer therapy. Patients with an index admission for HF who died of HF‐related causes (IAHF) and those with no index admission for HF who died of HF‐related causes (NIAHF) were compared. Methods and results: We performed a linked data analysis of cancer registry, death registry, and hospital administration records ( n  = 15 987). Index HF admission must have occurred after cancer diagnosis. Of the 4894 patients who were deceased (30.6% of cohort), 734 died of HF‐related causes (50.1% female) of which 279 (38.0%) had at least one IAHF (41.9% female) post‐cancer diagnosis. Median age was 71 years [interquartile range (IQR) 62–78] for IAHF and 66 years (IQR 56–74) for NIAHF. There were fewer chemotherapy separations for IAHF patients (median = 4, IQR 2–9) compared with NIAHF patients (median = 6, IQR 2–12). Of the IAHF patients, 71% had died within 1 year of the index HF admission. There was no significant difference in HF‐related mortality in IAHF patients compared with NIAHF (HR, 1.10, 95% CI, 0.94–1.29, P  = 0.225). Conclusions: The profile of IAHF patients who died of HF‐related causes after cancer treatment matched the current profile of HF in the general population (over half were aged ≥70 years). However, NIAHF were younger (62% were aged ≤69 years), female patients with breast cancer that died of HF‐related causes before hospital admission for HF‐related causes—a group that may have been undiagnosed or undertreated until death.